The importance of alternative host plants as reservoirs of the cotton leaf hopper, Amrasca devastans, and its natural enemies - Saeed, Rabia; Razaq, Muhammad; Hardy, Ian C.W. (Springer, 2015)
Many agricultural pests can be harboured by alternative host plants but these can also harbour the pests’ natural enemies. We evaluated the capacity of non-cotton plant species (both naturally growing and cultivated) to function as alternative hosts for the cotton leaf hopper Amrasca devastans (Homoptera: Ciccadellidae) and its natural enemies. Forty-eight species harboured A. devastans. Twenty-four species were true breeding hosts, bearing both nymphal and adult A. devastans, the rest were incidental hosts. The crop Ricinus communis and the vegetables Abelmoschus esculentus and Solanum melongena had the highest potential for harbouring A. devastans and carrying it over into the seedling cotton crop. Natural enemies found on true alternative host plants were spiders, predatory insects (Chrysoperla carnea, Coccinellids, Orius spp. and Geocoris spp.) and two species of egg parasitoids (Arescon enocki and Anagrus sp.). Predators were found on 23 species of alternative host plants, especially R. communis. Parasitoids emerged from one crop species (R. communis) and three vegetable species; with 39 % of A. devastans parasitised. We conclude that the presence of alternative host plants provides both advantages and disadvantages to the cotton agro-ecosystem because they are a source of both natural enemy and pest species. To reduce damage by A. devastans, we recommend that weeds that harbour the pest should be removed, that cotton cultivation with R. communis, A. esculentus, and S. melongena should be avoided, that pesticides should be applied sparingly to cultivate alternative host plants and that cotton crops should be sown earlier.